Dynamic hybridization between two spleenworts, Asplenium incisum and Asplenium ruprechtii in Korea - Kim, Hyoung Tae; Park, Sang Hee; Kim, Jung Sung (Frontiers in Plant Science, 2023)
Natural hybridization between Asplenium incisum and A. ruprechtii has been observed in Northeast Asia and its allotetraploid species, A. castaneoviride, was reported. However, hybridization process between the parental species and the origin of the allotetraploid taxon remain obscure. Additionally, the systematic affinities of the recently described hybrid A. bimixtum, considered to go back to hybridization of A. ruprechtii, A. trichomanes and A. incisum is unresolved due to its similarity to A. castaneoviride. The goals of this study were to: 1) investigate the hybridization between A. ruprechtii and A. incisum, 2) verify the origin of A. castaneoviride occurring in Korea, whether it independently arose from 2x sterile hybrids, and 3) elucidate the reliability of identifying A. bimixtum. Three genotypes, A. incisum, A. ruprechtii, and their hybrid, were identified based on the nuclear gene pgiC sequence and finally divided them into six types by ploidy levels: diploid A. incisum, A. ruprechtii, and four hybrid types (diploid A. × castaneoviride, triploid A. × castaneoviride, allotetraploid A. castaneoviride, and A. bimixtum). In the analyses of plastid DNA, all hybrids had an A. ruprechtii-type rbcL gene. In addition, the four plastomes of A. ruprechtii and the hybrids had high pairwise sequence identities greater than 98.48%. They increased up to 99.88% when a large deletion of A. x castaneoriviride (2x) collected from Buramsan populations was ignored. Notably, this large deletion was also found in triploid A. × castaneoviride and allotetraploid A. castaneoviride in the same populations. Sequence data of the nuclear and plastid genes showed that hybridization is unidirectional, and A. ruprechtii is the maternal parent. The large deletion of rpoC2-rps2 commonly found in the different ploidy hybrids of the Buramsan population suggests that the allotetraploid A. castaneoviride can be created independently from sterile hybrids. We assume that both polyploidization driving allopolyploidy and minority cytotype exclusion took place independently in the population, since A castaenoviride co-occurs with A. ruprechtii in small populations. Furthermore, it was also observed that an enlarged noncoding region in fern organelle (ENRIFO) of the plastome was found in the genus Asplenium.